Increased prevalence of fracture and hypoglycaemia in young adults with concomitant type 1 diabetes mellitus and coeliac disease. (23rd October 2017) - Thong, Eleanor P.; Wong, Phillip; Dev, Anouk; Ebeling, Peter R.; Teede, Helena J.; Milat, Frances
Summary: Background: Both Type 1 diabetes mellitus (T1DM) and coeliac disease (CD) are independently associated with reduced bone mineral density (BMD) and increased fracture risk. Whilst poorer glycaemic control and increased microvascular complications have been described, the literature examining bone health and fractures in adults with concomitant T1DM and CD (T1DM + CD) is limited. Objective: To evaluate fracture prevalence and explore associations with glycaemic control, hypoglycaemia and microvascular disease in T1DM + CD compared with T1DM alone. Methods: We conducted a retrospective cross‐sectional study of young adults with T1DM, who attended diabetes clinics at a large tertiary referral centre between August 2016 and February 2017. Clinical information, radiological and biochemistry results were extracted from medical records. Patients with comorbid chronic kidney disease, glucocorticoid use, hypogonadism and untreated hyperthyroidism were excluded. Results: A total of 346 patients with T1DM alone (median age 23 years) and 49 patients with T1DM + CD (median age 24 years) were included. Median age, gender distribution, BMI, haemoglobin A1c, daily insulin dose and serum 25‐hydroxyvitamin D levels were similar between groups. Higher adjusted fracture risk was observed in T1DM + CD compared with T1DM (12.2% vs 3.5%; OR 3.50, 95% CI 1.01‐12.12, P  = .01), yet BMD was only measured in 6% of patients. The adjusted risk of hypoglycaemia ≥2/week was greater for T1DM + CD (55% vs 38%, OR 3.28, 95% CI 1.61‐6.69, P  = .001); however, this was not independently associated with fractures. Replete vitamin D (≥ 50 nmol/L) was associated with less hypoglycaemia (OR 0.48, 95% CI 0.29‐0.80; P  = .005), but not with fractures. Conclusions: Coeliac disease status was independently associated with increased fracture prevalence in young adults with T1DM. Recurrent hypoglycaemia was also increased in T1DM + CD, although hypoglycaemia was not independently associated with fractures. Prospective studies are required to determine the long‐term impacts of CD on bone health and glycaemic control in patients with T1DM.